2016
DOI: 10.1142/s1793292016500442
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Mg Bimetallic Catalysts for Preparation of Multi-Walled Carbon Nanotubes from Polypropylene: Influence of the Ratio of Ni/Mg

Abstract: This study designs Ni-Mg bimetallic catalysts for preparation of multi-walled carbon nanotubes (MWCNTs) from polypropylene (PP). The study further investigates the in°uence of Mg content on the catalytic activity of Ni catalyst. It is found that bimetallic Ni-Mg catalysts have higher reduction temperature, smaller Ni particle size and improved stability. Consequently, the addition of Mg not only enhances the yield of MWCNTs, but simultaneously improves the morphology and graphitization of MWCNTs. The activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For promoting the size stability and catalytic activity of monometallic catalysts, Shen et al . prepared Al‐Ni and Mg‐Ni bimetallic catalyst to combine with organically modified clay for the synthesis of CNTs from PP . In our previous works, a kind of trimetallic catalysts, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For promoting the size stability and catalytic activity of monometallic catalysts, Shen et al . prepared Al‐Ni and Mg‐Ni bimetallic catalyst to combine with organically modified clay for the synthesis of CNTs from PP . In our previous works, a kind of trimetallic catalysts, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates that the presence of small amounts of amorphous MgO can impose proper carbon solubility in Ni–Mg catalysts for the growth of CNTs from PS. In Shen’s work, it was demonstrated that the MgO could effectively enhance the thermal stability and catalytic lifetime of Ni active phase. In this work, we further revealed that the presence of interaction between NiO and MgO, namely the formation of MgNiO 2 , played an important role for the control of carbon solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al reported a universal degradation additive (nanosized carbon black), which showed high synergetic efficiency for the one-step carbonization of PP, PE, and PS into CNTs with the presence of NiO . Recently, Shen et al reported two new carbonization catalysts (i.e., Ni/MgO and Ni/Al 2 O 3 ) and achieved a very high carbonization rate of ∼80% of PP with the help of OMMT. , In addition, Tang and Gong have done many works on the application of final obtained CNTs and the conversion of PP, PE, and PS into other carbon nanomaterials with one-step carbonization. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations